1939
DOI: 10.1002/jlac.19395400111
|View full text |Cite
|
Sign up to set email alerts
|

Über die Nebenalkaloide von Lobelia inflata

Abstract: W i e l a n d u. Mitarb., Nebenalkaloide von

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1956
1956
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…(K)-Allosedamine 18 was isolated from Lobelia inflata, 6,29 and the structural identification was reported by Marion 36 and co-workers on the basis of the first racemic synthesis (Scheme 13). It should be noted that these authors actually reported the structure of sedamine 24 (not found in Lobelia plants), which is a diastereoisomer of allosedamine 18.…”
Section: Synthesis Of Allosedaminementioning
confidence: 98%
See 2 more Smart Citations
“…(K)-Allosedamine 18 was isolated from Lobelia inflata, 6,29 and the structural identification was reported by Marion 36 and co-workers on the basis of the first racemic synthesis (Scheme 13). It should be noted that these authors actually reported the structure of sedamine 24 (not found in Lobelia plants), which is a diastereoisomer of allosedamine 18.…”
Section: Synthesis Of Allosedaminementioning
confidence: 98%
“…17 The hydroxylation of 28 by the addition of a molecule of water gave 3-hydroxy-3-phenylpropanoic acid 29, which has been isolated from Lobelia inflata. 6 b-Oxidation gave benzoylacetic acid 30, an important intermediate in the biosynthesis. Feeding experiments have been used to show that phenylalanine 25, trans-cinnamic acid 28, and 3-hydroxy-3-phenylpropanoic acid 29 are all intermediates in the biosynthetic route and have consequently validated this pathway.…”
Section: Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…(+)-Sedamine 1, a piperidine alkaloid first isolated from Sedum acre [1] and later from all of the sedum species together with its (-)-enantiomer [2] displays a wide range of physiological activities. (+)-Sedamine finds its use in the treatment of cognitive disorder [3]; it has also been used for the treatment of some respiratory illness and also acts as an antagonist [4].…”
Section: Introductionmentioning
confidence: 99%
“…Visual dissection of its nucleus (dotted line) leads to two fragments, C6-C2-C,N, whose skeleton corresponds to that of some simpler Lobelia alkaloids, 8-phenylnorlobelol (4) (6) and 8-phenyllobelol (5) (6), which occur in Lobelia injiata. Even though such monomeric structures have not hitherto been found in L. cardinalis, the hypothesis is biogenetically attractive, that the lobinaline skeleton originates by dimerization of a suitably functionalized C6-C2-C,N monomer.…”
Section: Introductionmentioning
confidence: 99%